TORT VICTIM’S ABILITY TO PROFIT FROM THE PROCEEDS OF INSOLVENT TORTFEASOR’S LIABILITY INSURANCE - Yasser Mandela; I Ketut Dharma Putra Yoga (Jurnal Ius Constituendum, 2020)
This article describes and examines whether the tort victim can profit from the proceeds of the tortfeasor’s liability insurance. This article aims to reflect on which approach, either in common or civil law, provides more access for the tort victim to profits from the proceeds of insolvent tortfeasor’s liability insurance policy. The method used in this research is comparative research. The result of this research showed that the status of insurance proceeds becomes debatable because the tort victim (as the claimant) will have no better rights than any other unsecured creditors during insolvency proceedings. This is regardless of the fact that the tortfeasor already got a fund, albeit indirectly through the insurer, to compensate the tort victim’s losses. In relation to this issue, the United Kingdom has adopted the Third Parties (Rights against Insurers) Act 2010 which gives right for tort victim to directly claim for compensation against tortfeasor’s liability insurer in the event of tortfeasor’s insolvency. Meanwhile, the Indonesian legal system provides no clear legal protection to the tort victim. Thus, in the event of insolvency, the tort victim cannot obtain compensation from the insurer, but only from tortfeasor’s bankruptcy estate as part of creditors’ debts. Furthermore, as an unsecured creditor, the tort victim will obtain the debtor’s bankruptcy estate after all secured creditors have received their payment.